Fire Protection Philosophy - Mutadi; Munaji (Journal of Emerging Innovations in Engineering, 2025)
Lashing for cargo securing transportation onshore is to secure the heavy module Structure during transported by using trailer TRAILER Self Propelled Module Transporter is safely. The analysis of lashing should consider for the transverse  force in turning condition, Longitodinal force in breaking and acceleration condition. The weight of Structure is 25.774 mt metric tonwill transported by TRAILER with 4 axle, has speed 0.5 km/h and acceleration 0.07 m/s2, time taken to accelerate is 2 s. The environment condition is the wind speed is 10 m/s. The capacity of lashing is 0,5 5 mt. The result from the site activity  of the transportation of Module Structure with using TRAILER is succsessfuly and safely. The module Structure has the total transverse securing  force 2.49 mt  greater than total transverse sliding force 0,63 mt, the longitudinal securing force 2.49 mt is greater than total longitudinal sliding force 0.53 mt. The module Structure has the totals longitudinal force is 2.49 mt greater than total longitudina sliding force 0.48 mt. .